2019
DOI: 10.1111/jdv.15387
|View full text |Cite
|
Sign up to set email alerts
|

A potential contribution of trappin‐2 to the development of vasculopathy in systemic sclerosis

Abstract: Background Trappin-2/pre-elafin is an endogenous inhibitor of human neutrophil elastase involved in inflammation, innate immunity and vascular remodelling, which consist of the complex pathological process of systemic sclerosis (SSc).Objectives To clarify the potential role of trappin-2 in SSc.Methods Serum trappin-2 levels were determined by enzyme-linked immunosorbent assay in 51 SSc and 18 healthy subjects. Trappin-2 expression was evaluated in SSc lesional skin and cultured endothelial cells treated with F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
(94 reference statements)
1
6
0
Order By: Relevance
“…For instance, endothelial cell–specific Fli1 knockout mice spontaneously develop the histological and functional alterations characteristically seen in SSc vasculopathy, such as arteriolar stenosis, capillary dilation and increased vascular permeability 23 . Furthermore, many properties are shared by Fli1‐deficient endothelial cells and SSc endothelial cells 23‐29 . Therefore, we examined whether gene silencing of FLI1 affects VASH‐1 expression in HDMECs, but no significant change was observed (1.00 ± 0.13 [AU] versus 1.06 ± 0.05 [AU], p = 0.39; Fli1 knockdown efficiency, 82.5% [data not shown]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, endothelial cell–specific Fli1 knockout mice spontaneously develop the histological and functional alterations characteristically seen in SSc vasculopathy, such as arteriolar stenosis, capillary dilation and increased vascular permeability 23 . Furthermore, many properties are shared by Fli1‐deficient endothelial cells and SSc endothelial cells 23‐29 . Therefore, we examined whether gene silencing of FLI1 affects VASH‐1 expression in HDMECs, but no significant change was observed (1.00 ± 0.13 [AU] versus 1.06 ± 0.05 [AU], p = 0.39; Fli1 knockdown efficiency, 82.5% [data not shown]).…”
Section: Resultsmentioning
confidence: 99%
“…However, as shown in the immunohistochemical analysis, VASH‐1 expression in dermal small vessels was comparable between SSc patients and healthy controls. Since the immunohistochemical analysis is generally semi‐quantitative, we focused on the effect of Fli1 deficiency, a key predisposing factor to induce a large part of SSc‐specific property in endothelial cells, 23‐29 on endothelial VASH‐1 expression. FLI1 siRNA did not alter the expression of VASH1 mRNA in HDMECs, further supporting our conclusion described above.…”
Section: Discussionmentioning
confidence: 99%
“…However, they observed increased serum trappin-2 levels in SSc patients with digital ulcers and elevated right ventricular systolic pressure, as well as enhanced trappin-2 expression in small vessels of SSc lesional skin, suggesting that trappin-2, the precursor of elafin, plays a role in the vasculopathy in SSc. [ 15 ] Furthermore, there is substantial evidence from pre-clinical studies that indicates elafin has beneficial effects on various vascular injury and inflammation models. [ 16 ] These findings may also have implications on the role of elafin in BD, considering the role of endothelial dysfunction and vasculitis in its pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an epithelial host defense protein, ela n was recognized as a possible serum marker modulated in multiple pathological conditions, including brosis and vascular remodeling (3). Ela n and its precursor trappin-2 are inhibitors of human serine proteases of the chelonianin family (4).…”
Section: Introductionmentioning
confidence: 99%
“…Elgharib et al showed a statistically signi cant correlation between serum ela n levels and Psoriasis Area Severity Index (PASI) and between in ammation markers such as C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) (6). Furthermore, it was revealed that ela n may serve as a useful indicator of interstitial lung disease in SSc patients as well as be the biomarker of skin GvHD (3). The previous observations suggested that ela n can help in predicting transplant survival and response to treatment in acute GvHD (aGvHD) (7,8).…”
Section: Introductionmentioning
confidence: 99%